Pengaruh Implementasi Kurikulum Merdeka Belajar Pada Mata Pelajaran Fiqih Terhadap Kemampuan Berpikir Kritis Peserta Didik Di Mts Negeri 2 Bandar Lampung - Devi Sela Eka selvia; Siti zulaikhah, Alinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted at MTs Negeri 2 Bandar Lampung. This study aims to find out whether there is an influence of the implementation of the independent learning curriculum on the critical thinking ability of students at MTs Negeri 2 Bandar Lampung. The type of research used is a quantitative approach with Expost-Facto research methods.The population is all grade VIII students at MTs Negeri 2 Bandar Lampung which consists of 462 people. Sampling was carried out using random sampling techniques. The sample used was 46 people. The data collection techniques used are questionnaire dissemination, observation and documentation. So that the data to be obtained is quantitative data. Primary data was obtained directly from the distribution of questionnaires from respondents in the field. Meanwhile, secondary data was obtained from observations, documentation, and theories from literature, background documentation, and school activities at MTs Negeri 2 Bandar Lampung. The results of this study show that there is a positive and significant influence in the implementation of the independent learning curriculum on the critical thinking ability of students at MTs Negeri 2 Bandar Lampung, which can be seen in the calculation of the correlation coefficient and the T test. So that from the acquisition of R calculation with a positive value and the acquisition of a Tvalue of 4.261 compared to Ttable 1.678, so that the Tcount > Ttable, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted, which means that there is a positive and significant influence.